2016
DOI: 10.1111/jnc.13624
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide Y (NPY) in cerebrospinal fluid from patients with Huntington's Disease: increased NPY levels and differential degradation of the NPY1–30 fragment

Abstract: NPY) levels in human cerebrospinal fluid (hCSF) from HD patients (Control n = 10; early HD n = 9; mid HD n = 11). As this antibody-based detection of NPY may provide false positive differences as a result of the antibody-based detections of only fragments of NPY, the initial finding was validated by investigating the proteolytic stability of NPY in hCSF using matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF-MS) and selective inhibitors. A comparison between resulting NPY-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 96 publications
0
7
0
Order By: Relevance
“…MERGL levels seemed to be affected by antipsychotics in the former study, but we could not find differing levels of PENK in the participants using antipsychotics. Contrary from the GABA‐ and enkephalinergic MSNs, neuropeptide Y (NPY)‐containing interneurons are spared in HD and higher levels of NPY have been reported in CSF of HD patients 23 . The authors suggested that a ratio between NPY and dynorphin‐A or enkephalin peptides could serve as a biomarker for HD onset or disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…MERGL levels seemed to be affected by antipsychotics in the former study, but we could not find differing levels of PENK in the participants using antipsychotics. Contrary from the GABA‐ and enkephalinergic MSNs, neuropeptide Y (NPY)‐containing interneurons are spared in HD and higher levels of NPY have been reported in CSF of HD patients 23 . The authors suggested that a ratio between NPY and dynorphin‐A or enkephalin peptides could serve as a biomarker for HD onset or disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility is that some large hNSCs could have evolved into NPY interneurons. Interestingly, in HD, MSNs expressing NPY are spared and their numbers are even upregulated in HD patients (Wagner et al, 2016). Based on passive and active membrane properties, some cells also differentiated into large cholinergic interneurons.…”
Section: Ultrastructural Evidence That Hnscs Establish Synaptic Contamentioning
confidence: 99%
“…Fragment N‐224 was significantly increased in AD patients, and increase of its abundance was related to a decrease in cognitive performance over time . In a similar way, the cleaved forms of neuropeptide Y have been studied as markers for Huntington's disease . The use of peptidomic approaches is rapidly expanding, and other body fluids on top of those previously mentioned, such as saliva and sweat, are also being tested as sources of proteolytic biomarker fragments …”
Section: Discovery Of Protease Substratesmentioning
confidence: 99%